ANTIBACTERIAL ACTIVITY OF BRYOPHYLLUM PINNATUM AGAINST CLINICAL ISOLATES OF ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIA FROM URINARY TRACT INFECTION PATIENTS (FUDMA JOURNAL OF SCIENCES, 2022)
The emergence and spread of resistant strains of bacteria to routinely used antibiotics has made it imperative to continuously search for alternatives that can be used to cure infections, so as not to return to pre-antibiotic era. Plants are known to contain bioactive compounds that can be explored and used in the treatment of infection. The study investigated the antibacterial activity of ethanolic extracts of dried leaf extracts of Bryophyllum pinnatum against clinical isolates of Escherichia coli and Klebsiella pneumoniae from urinary tract infection patients attending Shehu Muhammad Kangiwa Medical Centre. The photochemical screening of the crude extracts of Bryophyllum pinnatum (leaf of life) carried out using standard procedures described by Trens and Jens 2002, revealed the presence of Saponins, Flavonoid, Terpenoids, Alkaloids, Phenol and Tannins . The antibacterial activity of the extracts was carried out using agar cup diffusion method. Four concentrations (200,100, 50 and 25mg/ml) of the extract were tested against Escherichia coli and Klebsiella pneumoniae. The zones of inhibition measured at 200,100, 50 and 25mg/ml were: 00,00,00 and 00 mm respectively. The extracts  therefore showed no antibacterial activity against the isolates at all the four concentrations tested. The results of this study proofs that the ethanolic extract of  B. pinnatum leaves has no effect on E. coli and K. pneumoniae isolated from patients with Urinary Tract Infection, and hence cannot be used to treat infections caused by these bacteria.
Keywords: Bryophyllum pinnatum, Escherichia coli, Klebsiella pneumoniae, Antibacterial activity